An early health technology assessment of 3D anatomic models in pediatric congenital heart surgery: potential cost-effectiveness and decision uncertainty. (3rd September 2021) - Tack, Philip; Willems, Ruben; Annemans, Lieven
ABSTRACT: Background : Three-dimensional anatomic models have been used for surgical planning and simulation in pediatric congenital heart surgery. This research is the first to evaluate the potential cost-effectiveness of 3D anatomic models with the intent to guide surgeons and decision makers on its use. Method : A decision tree and subsequent Markov model with a 15-year time horizon was constructed and analyzed for nine cardiovascular surgeries. Epidemiological, clinical, and economic data were derived from databases. Literature and experts were consulted to close data gaps. Scenario, one-way, threshold, and probabilistic sensitivity analysis captured methodological and parameter uncertainty. Results : Incremental costs of using anatomical models ranged from −366€ (95% credibility interval: −2595€; 1049€) in the Norwood operation to 1485€ (95% CI: 1206€; 1792€) in atrial septal defect repair. Incremental health-benefits ranged from negligible in atrial septal defect repair to 0.54 Quality Adjusted Life Years (95% CI: 0.06; 1.43) in truncus arteriosus repair. Variability in the results was mainly caused by a temporary postoperative quality-adjusted life years gain. Conclusion : For complex operations, the implementation of anatomic models is likely to be cost-effective on a 15 year time horizon. For the right indication, these models thus provide a clinical advantage at an acceptable cost.